The Development of a Prediction Equation to Estimate Resting Metabolic Rate of Healthy College-aged Students. - Vetterkind, Brian; Schommer, Paula; Kimmons, Amanda; Ekholm, Amanda (My University, 2009)
Resting Metabolic Rate (RMR) reveals how many calories are burned daily before considering any movement. Since RMR typically accounts for the largest proportion of daily energy expenditure, it is an important variable to quantify in anyone trying to control bodyweight. This research project will focus on various correlations between body composition and RMR.
Color poster with text, images, table, and graph.
Keywords: Metabolism--Regulation; Body composition--Physiological aspects; Low-calorie diet--Physiological effect; High-calorie diet--Physiological effect; Exercise--Physiological aspects; Posters